CONTRIBUTION OF SOCIAL SCIENCE IN THE FORMATION OF STUDENT CHARACTER BASED ON PANCASILA STUDENT PROFILE - Marsini (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This study aims to analyze the integration of social sciences in student character education based on the Pancasila Student Profile. A qualitative approach with a case study method was used to collect data through observation, in-depth interviews, and document analysis in several secondary schools in Indonesia. The results of the study show that the integration of social sciences is effective in instilling character values such as mutual cooperation, tolerance, diversity, independence, and critical thinking in students. Teachers play a central role as facilitators, linking social science materials with Pancasila values contextually. However, the challenges in the implementation of this program include limited resources, time, and teacher competence. These findings suggest that systemic support, including ongoing teacher training and the provision of adequate resources, is indispensable to improve the effectiveness of this integration. In conclusion, the integration of social sciences in character education based on the Pancasila Student Profile is a relevant and potential strategy in shaping the character of students who have noble character, have social awareness, and are ready to face global challenges. This study provides recommendations for the development of more flexible education policies and supports innovation in character learning in schools.